Penyuluhan Penanaman Pendidikan Moralitas Dan Nilai Pancasila Pada Anak - Kasmanto Rinaldi; Askarial Askarial (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Education in Indonesia has a character based on Pancasila. Each aspect of the character is based on the five precepts contained in Pancasila. This is considered very important for the Indonesian people because it can fortify themselves from various life phenomena that are not in accordance with values and morals. In the life of the Indonesian people must refer to Pancasila, and the existing moral values. This topic was chosen because considering the times, with globalization, moral values and Pancasila are increasingly being eroded by the times, so there is a need for education to the younger generation related to moral values and Pancasila. This service method is carried out in several stages, including the preparation stage and the stage of service implementation. The result of this service is that students know the moral and Pancasila values and how they are applied in everyday life. The purpose of this activity is to provide counseling or socialization to educate the students of SDN 005 Koto Damai about how to apply moral values and Pancasila values in everyday life.